The dynamics of the interaction between music and society in recorded popular Afrikaans music, 1900 – 2015. - Van der Merwe, Schalk Daniel (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.